2006
DOI: 10.1063/1.2369644
|View full text |Cite
|
Sign up to set email alerts
|

Angle dependent surface enhanced Raman scattering obtained from a Ag nanorod array substrate

Abstract: The angular dependence of surface enhanced Raman scattering (SERS) has been investigated for molecules adsorbed onto Ag nanorod array substrates fabricated using an oblique angle deposition technique. The strong SERS signal of trans-1,2-bis(4-pyridyl) ethene (BPE) was found to be strongly dependent on the incident angle of the excitation laser, with the maximum SERS intensity appearing at approximately 45° relative to the surface normal. A scattering model based on classical electrodynamic dipole radiation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 23 publications
3
78
1
1
Order By: Relevance
“…In contrast, the non-linearity in the thiophenol signal is quite different to silicon and therefore indicates anisotropic scattering from the SERS substrate. This observation is in keeping with previous results from a variety of SERS substrates [10,11]. Table 1 and was calculated according to the relationship given in the Appendix).…”
Section: Samples and Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…In contrast, the non-linearity in the thiophenol signal is quite different to silicon and therefore indicates anisotropic scattering from the SERS substrate. This observation is in keeping with previous results from a variety of SERS substrates [10,11]. Table 1 and was calculated according to the relationship given in the Appendix).…”
Section: Samples and Methodssupporting
confidence: 65%
“…4(c), the islands are 60 nm high and are placed on top of a solid 30-nm Ag layer. This second structure is somewhat analogous to the Ag nanorod on the Ag film substrate fabricated by Liu et al [11], also using oblique angle deposition. In both layouts, the structure is illuminated by an x-polarized linear plane-wave source, tilted by an angle φ with respect to the z-axis, to highlight the contribution of waves at the beam boundary angle in each of the cases listed in Table 1.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…28,29 Semicontinuous gold films support both localized and delocalized surface plasmon modes and have a much stronger local field enhancement than continuous thin film. 30 Both the metallic nanorod array and semicontinuous film are commonly used as SERS substrates due to large local field enhancements, [31][32][33][34][35][36][37][38][39] so the plasmon coupling in our nanorod-film hybrid is also expected to further enhance the local field and improve the sensitivity of SERS. In our studies, the long-axis SPR of the Au nanorod array is tuned by adjusting the rod length and the SPR of the semicontinuous Au film is tuned by controlling the sputtering deposition time.…”
mentioning
confidence: 99%
“…30 Both the metallic nanorod array and semicontinuous film are commonly used as SERS substrates due to large local field enhancements, [31][32][33][34][35][36][37][38][39] …”
mentioning
confidence: 99%
“…24 It is shown that the EM enhancement strongly depends on the particle size, shape, the separation of the particles, dielectric environment and arrangement. [25][26][27] Consequently, various methods have been taken to improve the EM enhancement of Ag NR array, including adjusting the length of Ag NR, varying the deposition angle, 28 changing the incident angle of the excitation laser 29 and altering the shape of NR. Recently, researchers have prepared plenty of structures like the square helical NR, 30 the L-shaped NR 31 and the folding straight Ag NRs into zig-zag structures.…”
Section: Introductionmentioning
confidence: 99%